2011
DOI: 10.1002/cjoc.201190198
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Conjugate Addition to Cyclic Enone Catalyzed by Cu‐NHC Complexes with C2 Symmetry

Abstract: A series of chiral, C 2 symmetric tridentate N-heterocyclic carbene precursors, containing two N-functionalized hydroxyl or alkoxyl groups, were synthesized. They were applied to catalyze the asymmetric conjugate addition of diethylzinc to cyclohex-2-enone and cyclopent-2-enone. Enantioselectivity of corresponding reactions can be accomplished with up to 76% ee, and 65% ee, respectively. Flip of major enantiomer was observed when different bases or copper sources were utilized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The metal-catalyzed conjugate addition of organic zinc reagents, which are mild alkylating reagents, to α,β-unsaturated carbonyls and esters, has been used extensively for C–C bond formation in organic synthesis [1,2,3,4,5,6,7]. The enolate intermediate formed in this process or by reductive addition can further react with an electrophile under the same reaction conditions, leading to a domino mode of reaction, which is highly desirable in organic synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…The metal-catalyzed conjugate addition of organic zinc reagents, which are mild alkylating reagents, to α,β-unsaturated carbonyls and esters, has been used extensively for C–C bond formation in organic synthesis [1,2,3,4,5,6,7]. The enolate intermediate formed in this process or by reductive addition can further react with an electrophile under the same reaction conditions, leading to a domino mode of reaction, which is highly desirable in organic synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…We envisioned that the coordinative ability of the heteroatom can be adjusted by changing its bonding. Previously, we have synthesized tridentate C 2 -symmetric imidazolinium salts 6 ( Figure 2 ) and their NHC precursors, which have two oxygen atoms in the arms, and found that their copper complexes could catalyze the asymmetric conjugate addition of Et 2 Zn to cycloalkenones efficiently [ 43 ]. To continue this work, we designed 7 , the unsaturated counterpart of 6 , to explore their applications in Suzuki-Miyaura coupling reactions, as it has been reported that Pd coordinated with unsaturated NHCs show higher reactivity than those with saturated NHCs [ 44 ].…”
Section: Introductionmentioning
confidence: 99%